Anisakiose: sororeatividade humana e desenvolvimento de um modelo experimental - Figueiredo Junior, Israel (2013)
Introduction: There is scientific evidence that several species of fish off the coast of Rio de Janeiro State are contaminated with larvae of the nematode Anisakis simplex. The seroepidemiology and clinical features of A. simplex infection in Brazil are poorly characterized. As a general rule, existing murine models for experimental study of anisakiasis have used introduction of the L3 larval form of the parasite or intraperitoneal inoculation with its antigenic extract to induce infection. Therefore, both to raise awareness of this nematode and to establish a model of acute and chronic intestinal infections, development of models involving introduction of living larvae via the oral route is essential. Aim: To investigate anisakiasis in humans and in an experimental mouse model. Specific aims: To evaluate seroreactivity to A. simplex in a population of asymptomatic adults and in a population of postpartum mothers and newborns through analysis of maternal and cord blood, to ascertain whether a relationship exists between rates of immunoreactivity to A. simplex and incidence of high-risk pregnancy, and to establish a mouse model of intestinal sensitization by means of introduction of live A. simplex larvae by intestinal gavage. Material and Methods: In humans, prospective cross-sectional study was conducted with administration of a structured questionnaire and collection of blood samples for measurement of IgG and IgE specific for somatic and excretory/secretory antigens of Anisakis spp. by ELISA and immunoblot. The chi-square test was used for analysis and odds ratios (OR) estimated with 95% confidence limits. A logistic regression model and principal components analysis were also used. In the experimental animal portion of the study, a device for peroral introduction of live larvae was developed at the Immunobiology laboratory of Universidade Federal Fluminense. A 3-cm longitudinal slit was fashioned at the distal end of a commercially available #4 gastric tube. The cut end of the tube was opened with the aid of ophthalmic forceps and a live larva was carefully placed in the tube. The forceps were then removed and the tube automatically closed over the larva for subsequent introduction into the gastric cavity of the animal. Blood samples were collected for measurement of IgG specific for somatic and excretory/secretory antigens of A. simplex by ELISA. Results: Of all volunteers in the first group, 20.9% (14 of 67) had a positive anti-Anisakis simplex IgE response when tested by ELISA; 13.4% (9 of 67) reacted to somatic antigen, 3.0% (2 of 67) to excretory/secretory antigens, and 4.5% (3 of 67) to both antigens. IgE positivity on ELISA was associated with the amount of fish intake (OR = 4.66; 95% CI = 1.30 to 16.67; Fisher s exact test, p = 0.019). Samples were also collected from 232 mothers, 135 recruited from a high-risk perinatal unit (UR) and 97 from a low-risk ward (USR). There were no significant differences in IgG levels measured by ELISA between mothers in the two groups (p=0.581). In mice, the gastric gavage method was effective for introduction of live larvae into the digestive tract. Seroreactivity values were significantly higher in infected mice, both for somatic and for excretory/secretory antigens, as compared with those of controls given saline alone by gavage (p<0.001, ANOVA and Tukey s post-hoc Test). Conclusion: Our results indicate an association between frequency of fish intake and systemic sensitization, and no direct association with allergies, which suggests previous contact with Anisakis simplex. In animals, direct delivery of larvae into the stomach is a simple and effective model of oral infection